The marketing planning workbook : effective marketing for marketing managers - Dibb, Sally. (International Thomson Business Press, 1996)
This book is about: Perspective; Core analyses; Analyses into strategy-Marketing strategy summary; Programmes for implementation; The marketing planning document; ...